Wargames from gladiators to gigabytes - Van Creveld, Martin (Cambridge University Press, 2013)
Where did wargames come from? Starting with the combat of David versus Goliath, passing through the gladiatorial games, tournaments, trials by battle, duels, and board games such as chess, all the way to the latest simulations and computer games, this unique book traces the subject in all its splendid richness. As it does so, it provides new and occasionally surprising insights into human nature.